SOCIAL STRUCTURE ANALYSIS TO IMPROVE SECURITY AND ORDER IN CLASS IIA MATARAM PRISON - Utama, Arfa Jalo Eka Prakasa; Simanjuntak, Meitisa Vanya (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The social structure, formed from both formal and informal interactions between inmates and officers, plays a crucial role in maintaining stability within prison environments. This article aims to analyze the existing social structure in Lapas (Correctional Facility) Class IIA Mataram and its influence on security and order within the facility. Using a qualitative approach, the study maps out the factors that shape the social hierarchy in the prison and how these social dynamics can be utilized to improve security conditions. The findings reveal that alongside formal regulations, unwritten social norms also significantly influence order within the prison. The combination of strict formal rules and the individual agency of inmates contributes to the reproduction of the existing social structure. Keywords: Social Structure; Prison Security; Inmate Hierarchy; Agency; Reproduction